1999
DOI: 10.1017/s0266466699155026
|View full text |Cite
|
Sign up to set email alerts
|

Cointegrating Regressions With Time Varying Coefficients

Abstract: This paper considers cointegrating regressions with time varying coefficients. The coefficients are modeled as smooth functions evolving over time. It is shown that they can be estimated nonparametrically, using suitably modified series estimators. Presented is the efficient method of estimation, which relies on simple prefiltering of the data and preestimation of the model. The test for the adequacy of model specification is also developed. Our model and statistical methods are applied to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 18 publications
6
152
0
1
Order By: Relevance
“…This is the seminal study that leads to an extensive using of TVC approach by many other works. They discussed the TVC approach that is developed by [21] in detail. They found that income elasticity varies over time, reflecting rapid development of the Korean economy.…”
Section: Previous Studies Using Time-varying Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the seminal study that leads to an extensive using of TVC approach by many other works. They discussed the TVC approach that is developed by [21] in detail. They found that income elasticity varies over time, reflecting rapid development of the Korean economy.…”
Section: Previous Studies Using Time-varying Methodsmentioning
confidence: 99%
“…An omitted variable or misspecification errors might be the examples for the violation of these features. Therefore, for conducting valid inferences on the parameters of the model, we use the canonical cointegrating regression (CCR) method proposed by [46], which was shown to be valid for a class of TVC models including (4) by [21]. We leave a more detailed discussion of the estimation procedure to [22].…”
Section: Time-varying Coefficient Cointegration Approachmentioning
confidence: 99%
“…Traditional co-integration tests are mostly based on the assumption of constant co-integrating vectors and this may be one of the reasons why in many cases co-integration has not been found among series that are seemingly co-integrated (as well underlined, among others, by Park and Hahn [12] ).…”
Section: Quantile Co-integration Regressionsmentioning
confidence: 99%
“…To see why Park and Hahn's (1999) approach may be useful to detect Markov switchingtype behavior, note that Park and Hahn (1999) assume that the elements of t are of the form ' (t=T ) ; where ' (r) has a Fourier ‡exible functional form. Let…”
Section: Time-varying Cointegrationmentioning
confidence: 99%
“…In addition, we analyze the test for the null hypothesis of cointegration proposed by McCabe et al (1997). Finally, we investigate whether or not the time-varying cointegration approach of Park and Hahn (1999) is able to detect Markov switching-type cointegration. While this is a more general formulation that detects smoothly changing cointegrating coe¢ cients, it could be able to detect our speci…cation, which only considers two possible states.…”
Section: Introductionmentioning
confidence: 99%